AB0077 Targeting Synovial Fibroblasts with Melanocortin Drugs. (15th July 2016) - Montero-Melendez, T.; Buckley, C.D.; Filer, A.; Turner, J.D.; Perretti, M.
Abstract : Background: The adrenocorticotropin hormone (ACTH) is a melanocortin (MC) peptide approved for the treatment of inflammatory conditions including gout and rheumatoid arthritis (RA) but undesired effects associated with continued elevated glucocorticoid production limit its clinical use 1 . Research in the last few years has focused on new strategies to develop melanocortin drugs without those side effects. The anti-inflammatory and protective effects of melanocortins on immune and joint cells - such as chondrocytes and osteoclasts – are well characterized. However melanocortin role and therapeutic potential on synovial fibroblasts (SF) are unknown. SF are key effector cells in RA, involved in leukocyte recruitment, cartilage destruction and RA progression and hence proposed as therapeutic targets for RA. Objectives: To characterize expression and function of the MC system in SF and explore its potential therapeutic application in synovial inflammation. Methods: Expression of the MC system in SF from RA patients was studied by PCR (receptors expression MC1 -MC5 ) and ELISA (endogenous peptides α-, γ-MSH and ACTH). MC-induced signalling was assessed by measuring cAMP production, Ca 2+ flux and ERK1/2 phosphorylation. Cytokine release was measured in supernatants by ELISA. The MC compounds studied include α-MSH (endogenous peptide, non-selective), DTrp (synthetic peptide, non-selective) and BMS-470539 (synthetic small molecule, MC1 selective). Results: SF expressed the receptors MC1, 3, 4, 5 and produced endogenous ACTH. MC targeting in these cells did not induce Gαs mediated cAMP production – of interest, as cAMP is the canonical MC pathway- but evoked increases in intracellular Ca 2+ and ERK1/2 phosphorylation suggesting a cell-specific differential signalling, not previously observed in other cell type. The consequences and molecular mechanism of this unusual signalling bias are not known. Treatment of SF with these drugs reduced cytokine release (IL-6, CXCL-5, CCL-2) as well as cell proliferation. Interestingly, the BMS-470539 compound induced cell senescence associated with p16 INK4a expression, measured by SA-β-galactosidase staining and immunofluorescence. This effect was only observed with BMS-470539 – and not by the peptide agonists – suggesting a prominent role of MC1 in MC-induced senescence in SF. On-going studies include the characterization of the BMS-470539-induced senescence associated secretory phenotype. Conclusions: We show herein that the MC system is functional in SF from RA patients and may be targeted pharmacologically for innovative anti-inflammatory approaches. SF are aberrantly activated in the inflamed synovium and MC treatment can reduce activation state (reduced cytokines) and proliferation. Detailed analyses of senescence-associated secretory phenotype induced by the BMS-470539 drug will help to understand the benefits of this approach on SF-associated synovial inflammation. References: Montero-Melendez T. ACTH: The forgotten therapy. Semin Immunol 2015;27(3):216–226. Disclosure of Interest: None declared